An update: epigenetic mechanisms underlying methamphetamine addiction - Liu, Mingxin; Si, Zizhen (Frontiers in Cell and Developmental Biology, 2024)
Methamphetamine (METH) is one of the most widely abused illicit drugs globally. Despite its widespread abuse, the effects of methamphetamine on the brain and the precise mechanisms underlying addiction remain poorly understood. Elucidating these biological mechanisms and developing effective treatments is of utmost importance. Researchers have adopted a multi-faceted approach, combining studies at the genetic, molecular, organ, and individual levels, to explore the epigenetic changes that methamphetamine use brings to an organism from both micro and macro perspectives. They utilize a comparative analysis of experimental animal data and clinical cases to ascertain differences and identify potential targets for translating METH addiction research from the experimental to the clinical setting. Recent studies have demonstrated that epigenetic regulation plays a pivotal role in neural mechanisms, encompassing DNA methylation, histone modifications (such as acetylation and methylation), ubiquitination, phosphorylation, and the regulation of non-coding RNA. These epigenetic factors influence an individual’s susceptibility and response to methamphetamine addiction by regulating the expression of specific genes. Specifically, methamphetamine use has been observed to cause alterations in DNA methylation status, which in turn affects the expression of genes associated with neuroreward pathways, leading to alterations in brain function and structure. Furthermore, histone modifications have significant implications for the neurotoxicity associated with methamphetamine addiction. For instance, the methylation and acetylation of histone H3 modify chromatin structure, consequently influencing the transcriptional activity of genes. Non-coding RNAs, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), also play a pivotal role in methamphetamine addiction by interacting with messenger RNAs (mRNAs) and regulating gene expression. To further advance our understanding, researchers employ advanced technologies such as high-throughput sequencing, chromatin immunoprecipitation sequencing (ChIP-seq), and RNA sequencing (RNA-seq) to comprehensively analyze epigenetic changes in both animal models and human subjects. These technologies enable researchers to identify specific epigenetic markers associated with methamphetamine addiction and to explore their functional consequences. This article reviews the role of these epigenetic mechanisms in methamphetamine addiction and discusses their potential implications for future clinical treatment strategies, particularly in the development of drugs targeting methamphetamine addiction. By deepening our comprehension of these epigenetic regulatory mechanisms, it is anticipated that targeted therapeutic strategies may be devised to reverse the gene expression alterations associated with methamphetamine addiction, thus enhancing the efficacy of addiction treatment and paving the way for future research in this domain.